HOW SOCIAL MEDIA MARKETING ACTIVITIES AFFECT PURCHASE INTENTIONS AND DECISIONS - Pradisti, Larisa; Roosdhani, Mohamad Rifqy; Komariyatin, Nurul; Huda, Nurul (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2024)
This study aims to analyze the influence of Social Media Marketing Activities (SMMA) on Purchase Decision (PD) through Purchase Intention (PI) at Sweet Mango Hijab store. The research method used is quantitative, with data collection through online surveys and direct interviews with 112 respondents who are familiar with the brand. The analysis results show that SMMA has a positive and significant impact on both Purchase Intention and Purchase Decision. These findings emphasize the importance of social media marketing strategies in influencing consumer behavior in the hijab market. The implications of this research suggest that companies should prioritize social media marketing activities to enhance consumer engagement and brand loyalty. Recommendations for Sweet Mango include investing in creative and interactive content, as well as regularly evaluating the performance of their social media marketing efforts. This study provides valuable insights into the relationship between social media marketing, purchase intention, and purchase decision in the hijab fashion industry.